2019
DOI: 10.1096/fj.201802270r
|View full text |Cite
|
Sign up to set email alerts
|

Naturally presented HLA class l–restricted epitopes from the neurotrophic factor S100‐β are targets of the autoimmune response in type 1 diabetes

Abstract: Type 1 diabetes (T1D) results from the destruction of pancreatic β-cells by the immune system, and CD8 + T lymphocytes are critical actors in this autoimmune response. Pancreatic islets are surrounded by a mesh of nervous cells, the peri-insular Schwann cells, which are also targeted by autoreactive T lymphocytes and express specific antigens, such as the neurotrophic factor S100-β. Previous work has shown increased proliferative responses to whole S100-β in both human T1D patients and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The HLA class I system serves an important role in the tumor immune response. This system comprises the classical HLA-A, -B and -C antigens, and the non-classical HLA-E, -F and -G antigens ( 60 ). Cancer cells can escape the CTL response by inhibiting HLA class I molecules ( 61 , 62 ).…”
Section: Immunosuppressive Microenvironment In Ecmentioning
confidence: 99%
“…The HLA class I system serves an important role in the tumor immune response. This system comprises the classical HLA-A, -B and -C antigens, and the non-classical HLA-E, -F and -G antigens ( 60 ). Cancer cells can escape the CTL response by inhibiting HLA class I molecules ( 61 , 62 ).…”
Section: Immunosuppressive Microenvironment In Ecmentioning
confidence: 99%
“…The full name of S100B gene is S100 calcium binding protein B. S100 protein is localized in the cytoplasm and/or nucleus of various cells and is involved in the regulation of many cellular processes, such as cell cycle progression and differentiation. Chromosomal rearrangements and altered expression of this gene have been linked to several neurological, neoplastic and other types of diseases, including Alzheimer's disease [9],Down syndrome [10],epilepsy [11],amyotrophic lateral sclerosis [12],melanoma [13]and type 1 diabetes [14] etc. Relevant studies have shown that S100B is associated with breast cancer prognosis, and high S100B expression predicts that breast cancer patients have a good long-distance metastasisfree survival [15],which is consistent with our analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood CD8 T cells responding to pancreatic antigens have been reported in both T1D patients and healthy controls. With the use of stimulation assays, the quantity of islet antigen-specific CD8 T cells is nearly universally reported to be greater in T1D patients than in healthy controls, 16,[23][24][25][26][27][28][29][30][31][32][33][34] and this extends to at-risk autoantibodypositive first-degree relatives 23,26 (Table 1). By contrast, by peptide-MHC multimer assays, which do not require functionality of a cell for its detection, the results are mixed.…”
Section: Identifying and Quantifying Islet Antigen-specific Cd8 T Cells In T1dmentioning
confidence: 99%